If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-24=3(v-9)
We move all terms to the left:
-24-(3(v-9))=0
We calculate terms in parentheses: -(3(v-9)), so:We get rid of parentheses
3(v-9)
We multiply parentheses
3v-27
Back to the equation:
-(3v-27)
-3v+27-24=0
We add all the numbers together, and all the variables
-3v+3=0
We move all terms containing v to the left, all other terms to the right
-3v=-3
v=-3/-3
v=1
| 5(x=4)=6x-8 | | 4x16= | | x+2x-11=41 | | 10-3d=-10+2d | | m÷(-105)=8 | | 2(x-14)=48 | | -7(a-4)=-7a+28 | | 3j+3=2j | | 2.71(g+7)=-8.13 | | 3/xx2=2/3x-4 | | X2+y=15 | | 3x-4(3x+2)=10 | | 8+x=60 | | 10=k/3-4+k/8 | | a-14=-17 | | 4(x-11)=-76 | | 1/3x-8=-9= | | 45=5(z–3) | | x3+12=19 | | -2(c-8)+-5=-1 | | .2x+.9=4.1 | | 4(x-8)=-32+4× | | 3x+72=5x-8 | | 3x+72=5x-37 | | -112q=-1456 | | −2x+6=22 | | 45=3(y-7) | | t2=449 | | 2u^2+4=100 | | 21Y=5(x)2 | | -1^2-1x=48.75 | | t9+2t18+4=10. |